2013
DOI: 10.5474/geologija.2013.004
|View full text |Cite
|
Sign up to set email alerts
|

Minerals of Pohorje marbles

Abstract: Metamorphism of relatively pure limestone and dolomite yields generally marble and dolomarble (Best, 2007). Impure carbonate protoliths that contain variable amounts of quartz grains and shaly material may include, in addition to calcite, dolomite and quartz, as well as diopside, tremolite, talc, phlogopite, wollastonite, calcic plagioclase, vesuvianite, forsterite and grossularandradite (Best, 2007). Therefore, the presence of the minor content of non-carbonate minerals corresponds to the chemistry and minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
(21 reference statements)
1
5
1
Order By: Relevance
“…Therefore, we can assume that marbles from Košenjak and Strojna are genetically different from those from Pohorje. This finding is in agreement with findings of Jeršek et al (2013) that Pohorje marble was metamorphosed from calcite prevailing protolith. Presence or absence of strontium could thus be used to distinguish marbles from Pohorje Mts.…”
Section: Common Rock-forming Mineralscalcite and Dolomitesupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, we can assume that marbles from Košenjak and Strojna are genetically different from those from Pohorje. This finding is in agreement with findings of Jeršek et al (2013) that Pohorje marble was metamorphosed from calcite prevailing protolith. Presence or absence of strontium could thus be used to distinguish marbles from Pohorje Mts.…”
Section: Common Rock-forming Mineralscalcite and Dolomitesupporting
confidence: 93%
“…Common accessory minerals are quartz, Narich plagioclase, tremolite, hornblende, diospide, mica, while garnet (mostly almandine), graphite, pyrite and chlorite, epidote, clinozoisite and serpentine group minerals occur rarely (Hinterlechner-Ravnik, 1971). Besides these, titanite, ferric oxides, vesuvianite, scapolite (Jarc & Zupančič, 2009;Jeršek et al, 2013), zircon, rutile and zoisite (Mrvar, 2013) have been found. Accessory minerals occur in bands, and are more frequent on the edges of marble lenses (Mrvar, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some grains of muscovite—KAl 2 (AlSi 3 O 10 )(OH) 2 (100, 196, 216, 263, 407, 704 and 751 cm −1 ), garnet (Raman bands at 167, 350, 500, 555, 635, 856, 912 and 1037 cm −1 indicate composition of almandine‐pyrope garnet solid solution—Fe 3 Al 2 (SiO 4 ) 3 ‐Mg 2 Al 2 (SiO 4 ) 3 ), epidote—Ca 2 Al 2 (Fe 3+ ;Al)(SiO 4 )(Si 2 O 7 )O(OH) (234, 273, 351, 453, 569, 603, 892 and 916 cm −1 ) and phyllosilicate minerals of chlorite group—(Mg,Fe) 3 (Si,Al) 4 O 10 (OH) 2 · (Mg,Fe) 3 (OH) 6 (204, 356, 547 and 679 cm −1 ) were also recognized. The composition of the aggregate suggests the use of local sand, as the geological background includes magmatic and metamorphic rocks overlain by dolomite from the Pohorje area (around 40 km from Ptuj) . In addition, a few ceramic grains were also observed in the investigated samples.…”
Section: Resultsmentioning
confidence: 81%
“…The composition of the aggregate suggests the use of local sand, as the geological background includes magmatic and metamorphic rocks overlain by dolomite from the Pohorje area (around 40 km from Ptuj). [16,17] In addition, a few ceramic grains were also observed in the investigated samples. The lime binder (Raman bands at 156, 282, 713 and 1087 cm À1 ) was fissured, and lumps of carbonated lime were also observed.…”
Section: Resultsmentioning
confidence: 86%